Efficacy and safety of anti-interleukin-1 therapeutics in the treatment of knee osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Lizhi Yu; Raoshan Luo; Gang Qin; Qinyan Zhang; Weiming Liang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective We aimed to evaluate the efficacy and safety of anti-interleukin-1 therapeutics, including IL-1 antibodies, interleukin-1 receptor antagonists (IL-1 Ras) and IL-1 inhibitors, for knee osteoarthritis (KOA) treatment. Methods Databases (Medline, Embase, Web of Science and CENTRAL) and ClinicalTrials.gov were systematically searched for randomized controlled trials (RCTs) of anti-interleukin-1 therapeutics from inception to August 31, 2022. The outcomes were the mean change in pain and function scores and the risk of adverse effects (AEs). Results In the 12 studies included, anti-interleukin-1 therapeutics were superior to placebo in terms of pain relief (standardized mean difference [SMD] =  − 0.38, 95% confidence interval [CI] =  − 1.82 to − 0.40, p < 0.001, I 2 = 77%) and functional improvement (SMD =  − 1.11, 95% CI =  − 1.82 to − 0.40, p = 0.002, I 2 = 96%). The incidence of any AE (risk ratio [RR] = 1.02, 95% CI = 0.88–1.18, p < 0.001, I2 = 76%) was higher following treatment with anti-interleukin-1 therapeutics than placebo, while no significant difference was found in the incidence of serious AEs (SAEs) or discontinuations due to AEs. Subgroup analyses showed that IL-1 antibodies and the IL-1 inhibitor provided pain relief (IL-1 antibodies: SMD =  − 0.61, 95% CI =  − 0.92 to − 0.31, p < 0.001; IL-1 inhibitor: SMD =  − 0.39, 95% CI =  − 0.72 to − 0.06, p = 0.02, I2 = 74.0%) and functional improvement (IL-1 antibodies: SMD =  − 1.75, 95% CI =  − 2.10 to − 1.40, p < 0.001; IL-1 inhibitor: SMD =  − 0.28, 95% CI =  − 0.83 to 0.27, p = 0.31, I 2 = 88%) superior to those of placebo, whereas IL-1 Ras did not. However, the IL-1 inhibitor increased the incidence of any AE (RR = 1.35, 95% CI = 0.92–1.98, p < 0.001, I 2 = 85%) but not the risk of SAEs or discontinuations due to AEs. IL-1 antibodies and IL-1 Ras showed no difference in safety compared with placebo. Conclusions Anti-interleukin-1 therapeutics could relieve OA-related pain and improve function, but is probably associated with an increased risk of adverse events. Specially, IL-1 antibodies and an IL-1 inhibitor could relieve OA-related pain and improve function, whereas IL-1 Ras could not. IL-1 antibodies and IL-1 Ras were relatively safe options, but IL-1 inhibitors were associated with safety concerns.